Community and Its Plastic Embodiments - Petrovsky, Helen V. (Actual Problems of Theory and History of Art, 2022)
How does the practice of contemporary art make us rethink the principles of classical aesthetics? This question is examined through a specific case study, namely, the sculptures of Vadim Sidur, an original Soviet artist. The paper formulates the concept of hieroglyphic sign that originates in the artistic practices themselves, indicating ways in which the contemporary theory of art might be further developed. Sidur’s sculptures are juxtaposed with G. E. Lessing’s Laocoon that interprets classical sculpture as striving for eternity, i.e., as subject to idealization and subordinated to the principle of beauty. What Sidur’s sculptures express, however, is not individual heroism, where pain is overcome for the sake of harmony, but collective pain and suffering that cannot be sublated –– harmonized –– in a work of art.In order to better understand Sidur’s sculptures, it is useful to turn to S. M. Eisenstein’s remarks. For Eisenstein, the hieroglyph is not only a combination of picture and concept, but also a “conflict” of the two, which is how he understands cinematic montage. The hieroglyph expresses something meaningful and universal by means of pictorial units. Elaborating this idea, one might suggest that symbolic mediation is discarded and that sculpture becomes a social sign of pain. Inseparable from the dynamic of social matter, such signs participate in it directly. Thus they challenge the linguistic model and reveal an irreducible community, in Sidur’s case –– a non-heroic community of those who share the experience of 20th century mass suffering. Hieroglyphic signs contradict autonomy and individuality typical of the classical philosophies of art.
Keywords: classical aesthetics; contemporary art; sculpture; hieroglyphic sign; montage; V. Sidur; G. E. Lessing; S. M. Eisenstein